The Correlation between Teacher Role and Student Perception of Kahoot! Usage in Reading Instruction - Niken Purwani; Sari Hidayati; Hengki Kris Sanjaya (ENGLISH FRANCA : Academic Journal of English Language and Education, 2026)
The traditional approach to teaching reading texts in senior high schools has often been met with a lack of enthusiasm from students. Moreover, learning and comprehending numerous English texts in the classroom might be very boring. Thus, students must complete tedious assignments, such as understanding the text, extracting the key ideas from each paragraph, and answering questions based on the given texts. As a result, educators are increasingly exploring alternative strategies to make reading instruction more interactive and engaging. Technological innovations have led to the development of diverse learning models, along with tools that can enhance the efficacy of the language teaching and learning process. Gamification is becoming increasingly widespread, particularly in technology-enhanced training, to motivate and engage students in the learning process. This study examines the integration of technology into classroom activities. Some teachers have initiated this technique to engage and stimulate student engagement in classroom activities, particularly during reading class. Kahoot! is a technology platform that has demonstrated significant value in the language classroom. It can serve as both a teaching instrument and an evaluative measurement. This study aims to evaluate the implementation of Kahoot! This quiz aims to enhance student engagement in reading assignments and examine how the teacher's role can effectively encourage student interaction by implementing Kahoot!  This study presents a small-scale survey conducted with 63 students at SMAN 1 Cilacap, documenting their language learning experiences while utilizing the Kahoot! Quiz for reading assignments. The research employed a questionnaire with twenty items on a five-point Likert scale. The results indicate that nearly all participants had positive experiences while learning to understand the texts using Kahoot! quiz. The majority of participants reported being actively involved in language learning while using Kahoot! This platform facilitates student engagement and active participation in the language acquisition processes. As a result, it offers a more profound and enriching language acquisition experience.